PENERAPAN KONSEP ESENSIAL GEOGRAFI PARIWISATA PADA DESTINASI RAJA AMPAT - Ridwan, Masri; Musawantoro, Muhammad; Eppang, Buntu Marannu; Sujawoto, Fitra Ananta; Kasim, Muh; Amirullah, Amirullah; Sianipar, Christina Indriani (Universitas Negeri Malang, 2024)
IMPLEMENTATION OF ESSENTIAL CONCEPT OF GEOGRAPHY TOURISM IN RAJA AMPAT, INDONESIAThis study aims to analyze the availability of essential concepts as materials for Tourism Geography courses through the use of Raja Ampat, Southwest Papua Province as a tourist destination. This research was operated with a qualitative approach, with interviews with local tour guides, surveys, and observations of geosite locations and literature review. The results of the research include: 1) the concept of location (absolute and relative), distance, pattern, affordability, morphology, and spatial relationships, 2) obtained spatial data with attributes of 29 geosite locations and three models of tourist movement in Raja Ampat destinations; 3) availability of materials in accordance with the final achievement needs of students of the Department of Travel and Department of Tourism Destinations at Makassar State Tourism Polytechnic. Developing a contextual textbook on Raja Ampat tourism geography is recommended as a reference book supplement.Penelitian ini bertujuan untuk menganalisis ketersediaan konsep esensial sebagai bahan materi mata kuliah Geografi Pariwisata melalui pemanfataan Raja Ampat, Provinsi Papua Barat Daya sebagai daerah tujuan wisata. Penelitian ini dioperasikan dengan pendekatan kualitatif, dengan wawancara kepada pemandu wisata setempat, survei, dan observasi lokasi geosite serta kajian pustaka. Hasil penelitian diantaranya: 1) konsep lokasi (absolute dan relatif), jarak, pola, keterjangkauan, morfologi, dan keterkaitan ruang, 2) data spasial dengan atribut 29 lokasi geosite serta tiga model pergerakan wisatawan di destinasi Raja Ampat; 3) ketersediaan materi sesuai dengan kebutuhan capaian akhir mahasiswa Jurusan Perjalanan dan Jurusan Destinasi Pariwisata di Politeknik Pariwisata Negeri Makassar. Pengembangan buku ajar kontekstual tentang Geografi Pariwisata Raja Ampat direkomensadikan sebagai suplemen buku referensi.